MORALITY AND LAW: Critics upon H.L.A Hart’s Moral Paradigm Epistemology Basis based on Prophetic Paradigm - Khudzaifah Dimyati; Absori Absori; Kelik Wardiono; Fitrah Hamdani (Faculty of Law, Universitas Jenderal Soedirman, 2017)
The research focuses on a critism study of epistemologycal basis of the relation between law and morality in H.L.A. Hart’s rational paradigm. It is according to prophetic paradigm which is based on philosophical approach. According to the analysis, it is concluded that Hart’s opinion is based on the epistemological basic assumptions including the primary and secondary rules; Value/Ethics including epistemological ethics such as autonomous, individual, procedural, and relative ethics while the prophetic paradigm is based on the epistemological assumptions in which Relative Morailty is the result of creation and will of absolute reality. Meanwhile, Norm of morality means the reality should be created by the competent will through a delegate with epistemological ethics such as the combination between reality of society and apocalyptical values. Keywords: Moral Concepts, Prophetic Paradigm and Rational Paradigm